Influence of Dolichoderus thoracicus (Hymenoptera: Formicidae) on cocoa pod damage by Conopomorpha cramerella (Lepidoptera: Gracillariidae) in Malaysia - See, Y. A.; Khoo, K. C. (Cambridge University Press, 1996)
The relationship between abundance of Dolichoderus thoracicus (Smith) and damage to cocoa pods caused by Conopomorpha cramerella Snellen was examined in a series of experiments. Pods were harvested from ant-abundant and ant-scarce plots and categorized into fully extractable, partially extractable and unextractable, the last category reflecting the most severe degree of C. cramerella infestation. An abundance of D. thoracicus was associated with significant reductions in the percentage unextractable pods but had little or no influence on the other two categories. Mean percentage pods infested was generally kept below 50% in ant-abundant plots and mostly exceeded the 50% level in ant-scarce plots. Other studies were: a survey of individual pods relating rate of infestation by C. cramerella to D. thoracicus abundance, an experiment which examined the effect of D. thoracicus exclusion on the rate of C. cramerella infestation, and a count of exit holes made by emerging prepupae of C. cramerella in relation to varying degrees of D. thoracicus abundance. The results showed a clear negative effect of D. thoracicus abundance on C. cramerella infestation rate. The results also indicated that the protection conferred by D. thoracicus was largely confined to the particular pod on which it was present. Rat damage, monitored as a subsidiary study, was higher in ant-scarce plots throughout the study period.